Factors Influencing COVID-19 Preventive Behavior among Older Adults in Eastern Thailand - Poonthawe, Patcharin; Junprasert, Suwanna; Toonsiri, Chanandchidadussadee; Rattanagreethakul , Somsamai; Intolo, Sakorn; Luecha, Trakulwong (NU Journal of Nursing and Health Sciences, 2023)
The COVID-19 pandemic has had a severe impact globally, particularly on the elderly due to reduced body functions and chronic illnesses. Health literacy is crucial in promoting preventive behavior. This study aims to identify COVID-19 preventive behaviors and health literacy levels among the elderly in eastern region of Thailand, as well as factors influencing COVID-19 preventive behavior. A cross-sectional study utilized multi-stage random sampling to survey 208 elderly participants aged 60 years and over in seven provinces of eastern Thailand. A questionnaire based on health literacy concepts was developed. The Content Validity Index (CVI) for this questionnaire was determined to be 0.83. Furthermore, the second and third parts of the questionnaire demonstrated reliability coefficients of 0.89 and 0.86, respectively. Data were collected from June to October 2021 and analyzed using descriptive statistics, correlations, and stepwise multiple regression. The study found that health self-management skills related to COVID-19, underlying diseases, decision-making on COVID-19 information, and access to COVID-19 information predicted the level of COVID-19 preventive behavior among the elderly in the eastern region by 53.1% (R2 = .531, F = 4.736, p = .031) with statistical significance at the level of .05. This study highlights the critical factors that predict COVID-19 preventive behavior among older adults in Thailand. Multidisciplinary care teams are vital for effective strategy implementation strategies. Nursing professionals should lead efforts to promote the health and well-being of older adults during the pandemic. Further research is needed to understand the impact of underlying diseases and family functioning on COVID-19 preventive behavior.